2018
DOI: 10.22159/ajpcr.2018.v11i8.25372
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Analysis and Evaluation of in Vitro Immunomodulatory Activity of Rhododendron Arboreum Leaves

Abstract: Objectives: The objectives of this study are to analyze phytoconstituents in Rhododendron arboreum leaves (qualitatively and quantitatively) and to estimate the immunomodulatory effects of extracts using different in vitro methods for intracellular and phagocytic killing potency of neutrophils, which are subsequent, involved in the process of phagocytosis by neutrophils.Methods: R. arboreum leaves extracts were separately extracted in 100% methanol, 50% methanol, and aqueous by a hot percolation technique usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 13 publications
2
8
0
Order By: Relevance
“…4). The literature survey result of the reported compounds from this research showed to have potent herbal drug resources [15]. This emphasizes the plant's importance in homeopathic alignment as a healthcare product.…”
Section: Results Of Peak Chromatogramsupporting
confidence: 51%
“…4). The literature survey result of the reported compounds from this research showed to have potent herbal drug resources [15]. This emphasizes the plant's importance in homeopathic alignment as a healthcare product.…”
Section: Results Of Peak Chromatogramsupporting
confidence: 51%
“…All the extracts were undergone preliminary phytochemical analysis to identify the nature of secondary metabolites such as alkaloids, carbohydrate, glycosides, saponins, steroids, terpenoids, phenolics, flavonoids and protein present in the plant [16].…”
Section: Preliminary Phytochemical Screeningmentioning
confidence: 99%
“…The different solvent extracts of the bark of Cascabela thevetia L. obtained were separately tested for the presence of various plant constituents such as alkaloids, flavonoids, glycosides, steroids, tannins, phenolic compounds, carbohydrates, saponins, triterpenoids, anthraquinones and fatty acids as per the standard procedure available [11,12].…”
Section: Preliminary Phytochemical Analysismentioning
confidence: 99%